2012
DOI: 10.1371/journal.pone.0041482
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Genes (DRD2/ANKK1-TaqA1 and DRD4-7R) and Executive Function: Their Interaction with Obesity

Abstract: Obesity is a multifactorial disease caused by the interaction between genotype and environment, and it is considered to be a type of addictive alteration. The A1 allele of the DRD2/ANKK1-TaqIA gene has been associated with addictive disorders, with obesity and with the performance in executive functions. The 7 repeat allele of the DRD4 gene has likewise been associated with the performance in executive functions, as well as with addictive behaviors and impulsivity. Participants were included in the obesity gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 74 publications
(95 reference statements)
3
74
2
6
Order By: Relevance
“…Results from the psychomotor performance tasks indicated significantly reduced performance in obese individuals [36]. On measures of processing speed, one study failed to find a difference on Symbol Digit Modalities Test performance between obese and healthy control groups [43]. The other study found scores on the WAIS Digit Symbol Substitution Subtest were significantly poorer for the obese group compared ORCP-376; No.…”
Section: Psychomotor Performance and Speedmentioning
confidence: 96%
See 2 more Smart Citations
“…Results from the psychomotor performance tasks indicated significantly reduced performance in obese individuals [36]. On measures of processing speed, one study failed to find a difference on Symbol Digit Modalities Test performance between obese and healthy control groups [43]. The other study found scores on the WAIS Digit Symbol Substitution Subtest were significantly poorer for the obese group compared ORCP-376; No.…”
Section: Psychomotor Performance and Speedmentioning
confidence: 96%
“…Average BMI ranged from 30.5 kg/m 2 [30] xxx.e12 C. Prickett et al [31], where averages were reported. Three of the studies included male participants only [32][33][34]; four studies assessed women only [35][36][37][38], while ten studies included both male and female participants [28][29][30][31][39][40][41][42][43][44]. Study design and comparison groups: Twelve studies were cross-sectional in design; four had cross-sectional and prospective components, with one case-control design.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms in DRD2 (dopamine receptor D2, also an inhibitory receptor) have been associated with increased risk for alcoholism (Noble et al 1998), pathological gambling (Lobo et al 2010), and other addictive/impulse-control behaviors in humans (Ariza et al 2012).…”
Section: Neuroreceptor Proteinsmentioning
confidence: 99%
“…Los pacientes con AN presentan una pobre fl exibilidad cognitiva evidenciada en su difi cultad para adecuar su comportamiento a las demandas ambientales Aloi et al, 2015); una débil coherencia central, que les lleva a ignorar los aspectos globales y salientes de una situación y centrarse en los detalles (Aloi et al, 2015;Weider, Indredavik, lydersen, y Hestad, 2016); y un proceso de toma de decisiones centrado en la búsqueda de gratifi caciones a corto plazo ignorando las consecuencias a largo plazo (Galimberti et al, 2013;Matsumoto et al, 2015). En los pacientes con bulimia nerviosa y trastorno por atracón se ha observado un estilo cognitivo caracterizado por la infl exibilidad mental, perseverancia y problemas de cambio de enfoque (Ariza et al, 2012;Mobbs, Iglesias, Golay, y Van der Linden, 2011).…”
Section: Introductionunclassified